Modeling And Simulation Of Wind Turbine For Partial Load Operation - Mohd Yassim, Halyani; Hussin, Mohamed Saiful Firdaus; M. S., Azizi; A., Tajul; R. F., Farhana (Asian Research Publishing Network (ARPN), 2016)
The purpose of this research is mainly to model a wind turbine with doubly fed induction generator (DFIG) and to investigate its behavior in partial load operation using computer simulation. System behavior analysis and simulation are two particular approaches applied in this research. The wind turbine model is developed whereby the behavior of its main components is described by mathematical model and transformed in simulation model in MATLAB/Simulink. The simulation model is carried out in partial load operation at a wind speed of 9 m/s. The physical quantities including generator speed, torque and electrical power output are measured and evaluated. By using variable speed generator, a wind turbine model with optimum power generation at wind speed between 4 m/s to 13 m/s is created. This research shows that if mathematical models represent the wind turbine accurately, then the proposed model can be used to observe the dynamic behavior of wind turbine precisely, efficiently and inexpensively. The simulation result is expected to be a reference for extending the knowledge of dynamic behavior of wind turbines and optimize the performance of future large-scale wind turbine systems.